Current management and future challenges in salivary glands cancer - Locati, Laura D.; Ferrarotto, Renata; Licitra, Lisa; Benazzo, Marco; Preda, Lorenzo; Farina, Davide; Gatta, Gemma; Lombardi, Davide; Nicolai, Piero; Vander Poorten, Vincent; Chua, Melvin Lee Kiang; Vischioni, Barbara; et al. (Frontiers in Oncology, 2023)
Salivary gland cancers (SGCs) are rare, accounting for less than 5% of all malignancies of the head and neck region, and are morphologically heterogeneous. The diagnosis is mainly based on histology, with the complementary aid of molecular profiling, which is helpful in recognizing some poorly differentiated, borderline, or atypical lesions. Instrumental imaging defines the diagnosis, representing a remarkable tool in the treatment plan. Ultrasound and magnetic resonance are the most common procedures used to describe the primary tumor. The treatment of SGCs is multimodal and consists of surgery, radiotherapy, and systemic therapy; each treatment plan is, however, featured on the patient and disease’s characteristics. On 24 June 2022, in the meeting “Current management and future challenges in salivary gland cancers” many experts in this field discussed the state of the art of SGCs research, the future challenges and developments. After the meeting, the same pool of experts maintained close contact to keep these data further updated in the conference proceedings presented here. This review collects the insights and suggestions that emerged from the discussion during and after the meeting per se.